2014
DOI: 10.1001/jamaoto.2014.406
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Salivary Gland Cancer Survival

Abstract: Importance Several recent studies have documented disparities in head and neck cancer outcomes for Black patients in the United States. However, few studies have been conducted to evaluate for differences in long-term survival from salivary gland cancer (SGCA) for racial/ethnic minorities compared to Whites. Objective To determine if patient race or ethnicity impact SGCA survival. Design, Setting, and Participants Retrospective survival analysis of all patients with SGCA from 1988–2010 in the National Canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 20 publications
3
29
2
Order By: Relevance
“…Several studies have reported disparities in various adult head and neck cancer outcomes for black patients . A prior study using the SEER database did find that black adults with salivary gland malignancies had poorer survival rates than whites . The disparity in survival was due primarily to poorer disease‐specific survival for blacks with mucoepidermoid and squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported disparities in various adult head and neck cancer outcomes for black patients . A prior study using the SEER database did find that black adults with salivary gland malignancies had poorer survival rates than whites . The disparity in survival was due primarily to poorer disease‐specific survival for blacks with mucoepidermoid and squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Race and median household income was not associated with survival in the multivariate analysis; however, the proportion of high school education or less in the patient's neighborhood was. Russell et al did not report socioeconomic factors, but demonstrated that after controlling for age, gender, and tumor characteristics, disease‐specific survival for African Americans was significantly worse than for Caucasians. Needless to say, the patterns of how race and socioeconomic factors interact and how these may combine to influence health outcomes are enormously complex and relevant, but beyond the scope of this article .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, death due to the diagnosed sinonasal cancer (SEER site recode: 22010) was considered as the event of interest, and death due to other causes was treated as a censoring event. 10 Patient characteristics were summarized using percentages for categorical variables, means and medians, standard deviations, and interquartile ranges for central tendency and spread on numerical variables. Unadjusted differences between racial/ethnic groups were compared using chi-square and Kruskal-Wallis tests where appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Given the reported survival disparities according to race and ethnicity for other head and neck cancer subsites, as well as cancers in other sites of the body, we conducted this study with the primary objective of determining whether or not race and ethnicity affect sinonasal cancer survival. [6][7][8][9][10][11][12][13] Methods…”
mentioning
confidence: 99%